2014
DOI: 10.1002/mnfr.201400059
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat alters the expression of cortistatin and ghrelin systems in the PBMCs of elderly subjects: Putative implications in the postprandial inflammatory response

Abstract: Our results suggest a potential relevant role of CORT/ssts and ghrelin systems in regulating PBMCs response to nutrient intake, which could help to explain the positive effects of n-3 PUFAs-enriched diets in reducing the inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…RNA extraction, quantification, reverse-transcription as well as the development, validation and application of qPCR to measure the expression levels of different human transcripts have been previously reported elsewhere by our group [ 41 45 ]. Total RNA was extracted from paraffin-embedded breast cancer samples, frozen xenografted tumors and cell lines using Trizol (Life Technologies, Barcelona, Spain) following the manufacturer's protocol and subsequently treated with DNase (Promega, Barcelona, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…RNA extraction, quantification, reverse-transcription as well as the development, validation and application of qPCR to measure the expression levels of different human transcripts have been previously reported elsewhere by our group [ 41 45 ]. Total RNA was extracted from paraffin-embedded breast cancer samples, frozen xenografted tumors and cell lines using Trizol (Life Technologies, Barcelona, Spain) following the manufacturer's protocol and subsequently treated with DNase (Promega, Barcelona, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…Venous blood from the participants (12 h overnight fast) was collected in tubes containing EDTA during the fat-rich meal test, at 0 and 4 h. PBMCs were isolated as previously described [ 21 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…500,000 cells/well from each subject were seeded on ultra-low attachment multi 12-well plates (Corning Costar, Sigma) and treated per duplicate with 10% baseline fasting and postprandial serum derived from control and incident-T2DM patients (specifically, we used serum form individuals that developed T2DM during the first two years of follow-up). After the incubation periods (4 and 24 h), PBMCs were centrifuged and RNA was extracted and isolated using TRI-reagent (Sigma) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The most widely studied functional compounds are polyunsaturated fatty acids. In this line, a large range of studies directly performed in humans have shown the ability of n‐3 polyunsaturated fatty acids (n‐3 PUFAs) to alter transcriptional profile in PBMC showing a less pro‐inflammatory environment and a decrease in the expression of pro‐inflammatory factors (Gahete et al., ; Tsunoda et al., ). Additionally, PBMC have been shown to reflect increased lipolytic capacity (increased expression of genes such as PPARα and CPT1A ), which occurs in different tissues in response to the intake of n‐3 PUFAs (Myhrstad et al., ; Radler et al., ).…”
Section: Pbc As a Surrogate Materials For Key Organs And Tissues In Numentioning
confidence: 99%